Application of Constructivist Approach by Kiyai in Arabic Language Teaching at Al-Falah Pesantren, Banjarbaru: An Active Learning Model to Enhance Arabic Language Skills - Nurdin Nurdin; Anwar Hafidzi (Magister Manajemen Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2023)
This research addresses the role of the constructivist approach in teaching Arabic at the al-Falah Islamic boarding school, Banjarbaru. This research used a qualitative approach with in-depth interviews and participatory observation as data collection methods. The results showed that the constructivist approach to learning Arabic at Pesantren al-Falah applies active learning methods, such as discovery learning and free expression. Kiyai, instructors, and dormitory leaders have created various programs and activities to improve student's language skills. The learning environment is not only limited to the classroom but also involves the dormitory, playground, kitchen, mosque, and other places. In addition, problem-solving and thinking skills are taught during the learning process. Overall, the Kiyai as a role model approach model effectively improves students' skills in Arabic in pesantren. This research contributes to developing the Arabic language in other pesantren in Indonesia.